(untitled) (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Modern business developments, particularly those related to batik, are changing extremely quickly. A greater degree of rivalry amongst businesses in their battle for customers was brought about by the rise of different types of Batik businesses, both big and small. As a result, businesses need to be able to employ strategy and approach as a weapon to defeat rivals. In the context of consumers acting as decision makers, competition such as this will stimulate consumer buying interest. The data analysis used in this study was quantitative, using questionnaires and surveys as a tool. Standard deviation was also used, along with inferential statistics from structural equity analysis of the model (SEM) using partial least squares (SEM-PLS) to examine the relationship between variables. There were 150 respondents total in the research sample, all of them were Bandung locals who had purchased Ganasan Subang Batik. The review’s aftereffects demonstrated that there was no discernible negative difference in the influence of variable X1 on factor Y when variable Z was involved. It was recognized that the intervention of variable Z would significantly and critically reduce the impact of variable X2 on factor Y.